HUBUNGAN KARAKTERISTIK IBU DAN KARAKTERISTIK RUMAH TANGGA DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK PADA IBU HAMIL DI NUSA TENGGARA TIMUR (ANALISIS DATA RISKESDAS 2018) - Rizkia Rachmi, (2023)
Chronic Energy Deficiency (CED) is an occurrence when a mother experiences a prolonged or long-term lack of energy intake, hence it is called chronic. Basic Health Survey (Riskesdas) 2018 stated that the prevalence of CED among pregnant women in Indonesia is 17.3%, significantly higher than that, the prevalence of CED among pregnant women in the East Nusa Tenggara Province (NTT) is 36.8%, thus indicating a very high public health problem. This study aims to investigate the relationship between maternal characteristics and household characteristics with the occurrence of CED among pregnant women in NTT. This research design is a cross-sectional study using secondary data from Basic Health Survey (Riskesdas) 2018 involving 387 pregnant women. Bivariate analysis was conducted using the chi-square test, and multivariate analysis utilized multiple logistic regression. The research findings revealed variables that were significantly associated with the occurrence of CED among pregnant women in NTT, including parity (p=0.002), maternal education (p=0.018), access to hospital healthcare facilities (mode of transportation) (p=0.032), and access to primary healthcare facilities (travel time) (p=0.032). The multivariate analysis identified parity as the most influential variable for the occurrence of CED among pregnant women (p=0.015; AOR=1.878). In conclusion, mothers with a parity of less than 2 or more than 3 children are at higher risk of experiencing CED during pregnancy in NTT.